Carcinomas of the ethmoid region in two pigs in the State of Rio de Janeiro - Inada, Tetsuo; Rezende, Ana M.L. de; Dobereiner, Jurgen (Pesquisa Agropecuaria Brasileira, 2014)
Both tumours showed expansive growth, and caused compression atrophy of the tissues adjacent to the ethmoid region. In both cases there was invasion of the paranasal sinuses but there were no metastases. On histological examination one case was diagnosed as a carcinoma simplex and the other as a mucus-secreting adenocarcinoma. It was not possible to determine with certainty the histogenesis of the adenocarcinoma, but the histochemical studies suggested that the tumour originated from the Bowman's glands of the olfactory mucosa. It was concluded that the two studied cases probably belong to the co called group of "enzootic ethmoidal carcinomas".